Identification of Distinctive Structural Changes in Polish Senior Income (2016–2024) - Dębicka, Joanna; Mazurek, Edyta; Stańczyk, Elżbieta (Identyfikacja wyróżniających się zmian w strukturze dochodów polskich seniorów (2016–2024), 2025)
Abstract: Population ageing is reshaping European economies, including Poland, and calls for analytical approaches capable of identifying structural changes in income composition among older individuals. The aim of this article is to demonstrate the applicability of a method for detecting distinctive structural changes in income sources, using seniors aged 50 and over in Poland as an empirical example. The analysis is based on EU-SILC microdata for the years 2016, 2020, and 2024, combining a structural similarity test with an approach that identifies distinctive relative changes in income composition. The application of the method shows that it captures income structure changes associated with both institutional and economic shocks, in particular the statutory retirement-age reform, implemented in 2017 and the COVID-19 pandemic. Among women aged 60–64, an increasing combination of pension income and earnings from work is observed, while men aged 65–69 display rising labour income despite formal retirement eligibility. During the pandemic period, the method reveals shifts in the relative importance of self-employment and selected social benefits, especially among older age groups and women, which are only partially reflected in standard similarity test results. From a practical perspective, the proposed approach may be useful for analysing income structures of ageing populations and for identifying subtle but economically meaningful changes relevant to pension policy and labour market measures. By illustrating the method using the case of seniors’ incomes in Poland, the study contributes to methodological discussions on the analysis of structural change in socio-economic research.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2025, Nr 23 (29), s. 1-13
Keywords: population ageing; income structure; identification of distinguishing changes; EU-SILC; silver economy; starzenie się społeczeństwa; struktura dochodów; identyfikacja wyróżniających zmian strukturalnych; srebrna gospodarka